2005
DOI: 10.1128/mcb.25.18.8074-8083.2005
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Schizosaccharomyces pombe F-Box DNA Helicase in Processing Recombination Intermediates

Abstract: In an effort to identify novel genes involved in recombination repair, we isolated fission yeast Schizosaccharomyces pombe mutants sensitive to methyl methanesulfonate (MMS) and a synthetic lethal with rad2. A gene that complements such mutations was isolated from the S. pombe genomic library, and subsequent analysis identified it as the fbh1 gene encoding the F-box DNA helicase, which is conserved in mammals but not conserved in Saccharomyces cerevisiae. An fbh1 deletion mutant is moderately sensitive to UV, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
92
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 56 publications
(55 reference statements)
5
92
1
Order By: Relevance
“…As expected, the deletion of fbh1 in a rad22D unsuppressed background restored damage resistance to wild-type levels. Interestingly, the fbh1D mutant also showed sensitivity to DNA-damaging agents, but only to higher doses (data not shown; see Morishita et al 2005;Osman et al 2005). These previous studies demonstrated that deletion of fbh1 impaired growth and viability, probably due to chromosome segregation defects.…”
Section: Resultsmentioning
confidence: 90%
“…As expected, the deletion of fbh1 in a rad22D unsuppressed background restored damage resistance to wild-type levels. Interestingly, the fbh1D mutant also showed sensitivity to DNA-damaging agents, but only to higher doses (data not shown; see Morishita et al 2005;Osman et al 2005). These previous studies demonstrated that deletion of fbh1 impaired growth and viability, probably due to chromosome segregation defects.…”
Section: Resultsmentioning
confidence: 90%
“…The mechanistic basis of the Srs2 function was elucidated by biochemical studies that revealed its ability to bind Rad51 and to dismantle the Rad51-ssDNA (single-stranded DNA) nucleoprotein filament, the key catalytic intermediate in recombination reactions (Krejci et al 2003;Veaute et al 2003;Sung and Klein 2006). To date, no apparent Srs2 ortholog has been identified in other eukaryotes, although the recently identified Fbh1 helicase shows some structural similarity to the Srs2 helicase family and studies in Schizosaccharomyces pombe suggest that Fbh1 plays a role in processing HR intermediates (Osman et al 2005;Morishita et al 2005). However, Fbh1-deficient DT40 cells show no prominent sensitivity to DNA damaging agents, and exhibit only a mild SCE phenotype (Kohzaki et al 2007).…”
mentioning
confidence: 99%
“…Previous data derived from studies in S. pombe have suggested that both the F-box domain and the helicase domain of Fbh1 are required for the repair of DNA damage in that organism, although the helicase function seems more critical 18,19 . Moreover, genetic analysis suggested that yeast Fbh1 acts downstream of Rad51 in the HR pathway 18,20 . Consistent with this, the level of Rad51 nuclear foci is greatly increased in Fbh1-deficient yeast, a phenotype that is also characteristic of FBH1-depleted human cells 15,21,22 .…”
mentioning
confidence: 99%